Effect of simplified wind girder modelling on MNA-LBA analysis of open steel tanks. (June 2023) - Słowiński, K.; Piekarczyk, M.; Dybeł, P.
Abstract: The MNA/LBA design methodology for metal shells, including open-top tank steel shells, plays an important role in the European Standard on Strength and Stability of Shell Structures. However, when using this design format, particular doubts as to the correctness of the obtained results may arise when simplifications are used in modelling of key elements of tank structures in order to improve modelling and numerical calculation processes. This paper presents the results of numerical studies that address the question of how the simplifications in the modelling of the primary wind girder affect the values of the elastic buckling resistance and the plastic reference resistance determined from linear bifurcation analysis (LBA) and materially nonlinear analysis (MNA), respectively. Forty-two computational models of wind-loaded open storage tanks with three height-to-diameter ratios and with variable or constant wall thickness of a cylindrical shell, equipped with six different representations of the wind girder, were investigated in order to provide guidelines in the above-mentioned scope. It has been proven that the applied simplifications in the modelling of the primary wind girder allows for relatively faithful representation of the reference models, i.e. models in which the stiffening ring was modelled using shell finite elements, in the LBA analysis. In turn, a varied influence of the applied simplifications in modelling on the results of the MNA analysis was observed. The obtained results indicated a limited range of applicability of the results of the materially nonlinear analysis for the formal assessment of the relative overall slenderness of the considered shells. Finally the obtained results allowed for the formulation of practical conclusions for the purposes of design of open-top steel tanks using the MNA/LBA methodology. Highlights: Buckling and plastic reference resistances are identified by LBA and MNA analyses. The results of the MNA analysis are of limited use for part of the numerical models. Beam elements allow for a faithful representation of the primary wind girder. Radial restraint should be limited to the shells with low or medium aspect ratio H / D.